Evaluation of an Element-Tagged Duplex Immunoassay Coupled with Inductively Coupled Plasma Mass Spectrometry Detection: A Further Study for the Application of the New Assay in Clinical Laboratory - Wencan Jiang (Molecules, 2020)
Background: Element-tagged immunoassay coupled with inductively coupled plasma mass spectrometry (ICP-MS) detection has the potential to revolutionize immunoassay analysis for multiplex detection. However, a further study referring to the standard evaluation and clinical sample verification is needed to ensure its reliability for simultaneous analysis in clinical laboratories. Methods: Carcinoembryonic antigen (CEA) and α-fetoprotein (AFP) were chosen for the duplex immunoassay. The performance of the assay was evaluated according to guidelines from the Clinical and Laboratory Standards Institute (CLSI). Moreover, reference intervals (RIs) of CEA and AFP were established. At last, 329 clinical samples were analyzed by the proposed method and results were compared with those obtained with electrochemiluminescent immunoassay (ECLIA) method. Results: The measurement range of the assay was 2–940 ng/mL for CEA and 1.5–1000 ng/mL for AFP, with a detection limit of 0.94 ng/mL and 0.34 ng/mL, respectively. The inter-assay and intra-assay imprecision were all less than 6.58% and 10.62%, respectively. The RI of CEA and AFP was 0–3.84 ng/mL and 0–9.94 ng/mL, respectively. Regarding to clinical sample detection, no significant difference was observed between the proposed duplex assay and the ECLIA method. Conclusions: The ICP-MS-based duplex immunoassay was successfully developed and the analytical performance fully proved clinical applicability. Well, this could be different with other analytes.